Identification of QTLs involved in destemming and fruit quality for mechanical harvesting of New Mexico pod–type green chile - Ortega, Franchesca; Hill, Theresa; Van Deynze, Allen; Garcia-Llanos, Armando; Walker, Stephanie (Frontiers in Plant Science, 2024)
Domestic production of pepper (Capsicum spp.) is shrinking while demand within the US is growing. Lack of availability and cost of labor often present an obstacle for domestic producers both practically and economically. As a result, switching to harvesting peppers mechanically is anticipated as a key strategy to help domestic producers compete in the international market.Mechanical harvest efficiency can be improved through breeding. One important trait that mechanical harvest compatible material should have is an easy destemming trait: low force separation of the pedicel and calyx from the fruit. To detect the genetic sources underlying a novel easy destemming trait for the purpose of future breeding efforts in New Mexico pod-type green chile, we performed QTL analysis on three F2:F3 populations, coming from three New Mexico pod-type varieties: 'NuMex Odyssey,' 'NuMex Iliad,' and 'NuMex Joe E. Parker,' each crossed with a parent with an easy destemming trait: MUC14. Genotyping was done through genotyping by sequencing (GBS) and phenotyping was done for destemming and fruit trait measurements. Correlations between measurements were found through the R package hmisc and QTL analysis was done through R/qtl. A strong relationship was seen between destemming and aspects of fruit morphology, particularly, destemming force and fruit width (Pearson's correlation coefficient r=0.75). Major QTLs for destemming and fruit size were discovered. Of these, the largest destemming force QTLs for all populations (PVE=34.5-69.9%) were on chromosome 10, and in two populations QTLs for destemming force were found on chromosome 3 (PVE=10.7-18.8%). Fruit size-related QTLs in all populations colocalized in these same areas on chromosomes 3 and 10. This suggests that fruit shape may be genetically linked to destemming, and breeders interested in selecting for easy destemming pepper will also have to pay attention to fruit size and shape.